CSR Index of Energy Sector Companies in Indonesia - Wahyudi, Heru; Lenni, Sandra Mey; Sutarto, Sutarto (International Journal of Energy Economics and Policy, 2024)
This research analyzes the pattern of Corporate Social Responsibility (CSR) disclosure in energy sector companies listed on the Indonesia Stock Exchange. With increasing regulations and global awareness about sustainable resources, energy companies in Indonesia are encouraged to adopt CSR practices. This study uses purposive sampling and checklist methods based on six categories of Global Reporting Initiative (GRI) indicators: economic, environmental, labor, human rights, social, and product responsibility. The research results show significant variations in CSR disclosure between companies, with the CSR Index ranging from 10.99% to 64.83%. The social community category at 8.88% and the product responsibility category at 7.44% had the lowest level of disclosure, reflecting the company’s lack of attention to these issues. In contrast, the environmental category at 14.83% and the labor category at 13.76% showed the highest level of disclosure, indicating the company’s focus on environmental issues and employee welfare. The suggestion from this research is that companies can increase awareness and commitment to CSR, as well as improve their social performance and product responsibility to achieve more responsible and sustainable business practices.